1996
DOI: 10.1039/jm9960601557
|View full text |Cite
|
Sign up to set email alerts
|

Dehydration–rehydration in magnesium vermiculite: conversion from two–one and one–two water layer hydration states through the formation of interstratified phases

Abstract: The dehydration-rehydration of Mg-vermiculite, as large flakes (7 x 5 x 0.1 mm3) and powder (< 80 pm), has been studied. Samples were treated in a sealed bomb at 140 and 100 "C for several days. After dehydration, they were rehydrated at room temperature. The samples were examined by X-ray diffraction, and the results are analysed here for the first time by the direct Fourier transform method. The resu!ts indicated the formation of two-water layer hydration states (14.4, 14.2, and 13.8 A phases), and one-layer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 17 publications
3
11
0
Order By: Relevance
“…At higher temperatures, only the phase with an interlayer distance of d = 11.5 A Ê persists. These results are in accordance with those of Reichenbach ad Beyer (1994) and Ruiz-Conde et al (1996).…”
Section: Chemical Analyses and Geological Settingssupporting
confidence: 95%
See 1 more Smart Citation
“…At higher temperatures, only the phase with an interlayer distance of d = 11.5 A Ê persists. These results are in accordance with those of Reichenbach ad Beyer (1994) and Ruiz-Conde et al (1996).…”
Section: Chemical Analyses and Geological Settingssupporting
confidence: 95%
“…In this study, three vermiculites from different geological settings, thus with different chemical compositions, have been analysed. Furthermore, the evolution of the hydration states with time and temperature, at these low pressures, have also been studied and compared with those at atmospheric pressure, reported previously (Collins et al, 1992;Reichenbach and Beyer, 1994;Ruiz-Conde et al, 1996). The interstrati ed states formed during the dehydration process, at these conditions, were analysed by the direct Fourier-transform method using the INTER program (McEwan et al, 1961;Ruṍz Amil et al, 1967;Vila and Ruṍz Amil, 1988).…”
Section: Introductionmentioning
confidence: 98%
“…Similar heating procedures at 250~ produced an irrational series of basal maxima (Figure 2). These results generally agreed with Mg-exchanged vermiculite behavior under heating (cf Collins et al 1992;Reichenbach and Beyer, 1994;Ruiz-Conde et al, 1996). Figure 3 shows X-ray patterns of different size-fractions of the studied sample.…”
Section: Resultssupporting
confidence: 75%
“…Peaks at 12.63 and 7.28 Å probably represent hydrophlogopite-like layers interstratification (Moore and Reynolds, 1989). The 12.63 Å phase is probably originated from twoand one-sheet hydrates (Collins et al, 1992;Ruiz-Conde et al, 1996;Marcos et al, 2003). Walker (1961) concluded that the 12.63 Å reflection is attributed to interstratifications between contracting and non-contracting phases.…”
Section: X-ray Diffraction Of Mineral Phasesmentioning
confidence: 98%